Comparison of Electrical Conductivity in Compounds of Carbon Black With Natural and Butadiene Rubbers - Erol Sancaktar; Satilmis Basan (Frontiers in Materials, 2019)
Carbon black (CB) filled butadiene (BR) (Cis-1,4-polybutadiene) and natural (NR) (Cis-1,4-polyisoprene) rubber compounds containing CB in 60–100 per hundred (phr) proportions were investigated for their pressure/time-dependent electrical conductivity. Due to their high deformability, the percolation thresholds for CB–BR and CB-NR compounds were functions of pressures (compression loads) applied. Resistivity of such compounds decreased with time and compressive load levels. Storage moduli, G', as well as the loss moduli, G” and the dynamic viscosities, η* of the compounds were evaluated to assess viscoelastic response of the compounds' conductivities under pressure. The storage and loss moduli values for both the CB-BR and the CB-NR compounds decreased with increasing strain levels, indicating that the rate of increase in conductivity is expected to increase at higher compressive loads. The storage moduli increased with increasing frequency (rate), indicating that the rate of increase in conductivity should be lower at higher rates of compressive load application. Comparison of variations in conductivity between the CB–BR and CB-NR compounds as functions of time and pressure, however, revealed that, overall, the conductivity levels are also strongly dependent on the nature of the molecular structure of these rubber materials and their initial interactions with CB during compounding, and the resulting dispersion levels of CB. Once such dispersion structure is established, the overall difference in conductivity levels for the CB–BR and CB-NR compounds remain approximately unchanged for given time and pressure conditions for the cases where high CB fill levels (~90 phr) are used and asymptotic conductivity values are reached. The experimental results revealed that because of the presence of higher number (~2-fold) of hydrogen side atoms on the linear BR chains, CB–BR compound forms more physical crosslinks (mostly due to hydrogen bonding) in comparison to the CB-NR compound resulting in more effective CB dispersion and higher conductivity. Such higher efficiency in CB dispersion and percolation in BR is further implied by higher conductivities despite higher G' and η* values for the CB–BR compound in comparison to the CB-NR compound.